Modeling and Analysis of Micro Gas Turbine Compressor Different Parts - ., Sinoj; Dev Anand, M.; Ramasamy, N. (International Journal of Engineering and Technology, 2018)
The work displayed in the report is an endeavor at planning a miniaturized scale turbine of a given measurement. Broad writing audit was done to contemplate the different perspectives and utilizations of small scale turbines. An appropriate outline methodology was looked over the accessible strategies to plan distinctive parts of miniaturized scale turbine. CATIA is utilized broadly to make parts with diff sorts of tasks. At that point every one of the parts are collected for making a total turbine in CATIA Get together area. At that point they are sending for fast prototyping.Â